2017
DOI: 10.1186/s12889-017-4307-7
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral antecedents for handwashing in a low-income urban setting in Bangladesh: an exploratory study

Abstract: BackgroundHealth programs commonly promote handwashing by drawing attention to potential fecal contamination in the environment. The underlying assumption is that the thought of fecal contamination will result in disgust, and motivate people to wash their hands with soap. However, this has not proven sufficient to achieve high rates of handwashing with soap at key times. We argue that handwashing with soap is influenced by broader range of antecedents, many unrelated to fecal contamination, that indicate to pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
3
5
0
Order By: Relevance
“…Results of our study showed that non-doers were more likely to say that it is very difficult to remember to perform the behavior and represents a barrier for them. This result is aligned with other previous WASH studies of Bangladesh (Rahman et al 2017;Parveen et al 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Results of our study showed that non-doers were more likely to say that it is very difficult to remember to perform the behavior and represents a barrier for them. This result is aligned with other previous WASH studies of Bangladesh (Rahman et al 2017;Parveen et al 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Results of our study showed that Non-doers were more likely to say that it is very difficult to remember to perform the behavior and represents a barrier for them. This result is aligned with other previous studies of Bangladesh in domestic, community and school-based WASH interventions (8,37).…”
Section: Discussionsupporting
confidence: 92%
“…The practice of keeping soap away from handwashing place may not be as common in urban settings, where latrines have a place to keep soap and water . Visual or tactile sensations (having hands that were sticky and covered in grease or oil) and activities of daily living (handling unwashed vegetables or starting a meal) are behavioural antecedents to handwashing , and it may be possible to incorporate these sensations to drive handwashing behaviours. A community‐based intervention study in India used disgust and nurturing among mothers as drivers of handwashing behaviour, and the observed prevalence of handwashing after the intervention was higher than the prevalence observed in this study.…”
Section: Discussionmentioning
confidence: 99%